Multi-agent-based simulation XIX : 19th International Workshop, MABS 2018, Stockholm, Sweden, July 14, 2018, Revised selected papers /: 19th International Workshop, MABS 2018, Stockholm, Sweden, July 14, 2018, Revised selected papers. (2019) - Unknown
No abstract available